RANCANG BANGUN SISTEM PENGUKURAN SUHU TUBUH MANUSIA OTOMATIS TANPA KONTAK FISIK DENGAN SENSOR SUHU MLX90614 BERBASIS ARDUINO UNO PADA BILIK DISINFEKTAN - Rizki Pardamean Sinaga; Susilo Susilo; Bambang Widodo (Prodi Teknik Elektro FT UKI, 2020)
In the end of 2019, the world have been experiencing a pandemic event until today, the wide spread of coronavirus which is scientifically known as covid-19. One of the symptoms that emerges due to the spread of this virus is the human body is not in a normal temperature, which is more than 37.5°C. Therefore, the measurement of human body temperature is now a mandatory protocol in order to preventing the spread of the Covid-19 virus. This paper discusses about a tool that could measure the human body temperature without any physical contact is needed using The MLX90614 temperature sensor series based on Arduino Uno in the disinfectant booth. The type of sensor that is used in the manufacture of this tool is the MLX90614 temperature sensor, this sensor is known as a non-contact temperature sensor used in measuring the temperature of the human body without direct contact with the object. The purpose of making this tool is to make the measurement of human body temperature can be used in a faster way and to minimize a face-to-face contact with other human. This tool has an alarm that will work if the temperature is on ≥37.50C and then the alarm will be active for 10 seconds and if the temperature is <37.50C the alarm will be active for 1 second so that it’s able to detect people who are allowed or not allowed to enter the building, with a measurement distance of between 0.1 - 10 cm with accuracy level of 99.91%.